U–]Pb zircon ages and metamorphic conditions of mafic granulites from the basement of the southern Brasilia Orogen, Campinas-SP region - Amaral, Wagner S.; Santos, Felipe H.; Bravo, Jozias C.S.; Fedel, Henrique S.; Luvizotto, George L. [UNESP]; Godoy, Daniel F. [UNESP] (Elsevier, 2019)
In the southern Brasília Orogen, slices of an intensively reworked Paleoproterozoic basement occur. These are partially covered by a Neoproterozoic sequence of high-metamorphic grade, corresponding to the Socorro–Guaxupé Nappe and intruded by several Neoproterozoic plutonic rocks. In this contribution, we present thermobarometric and geochronological data of the basement rocks in the Campinas city, southern part of the Brasilia Orogen. The occurrence of mafic granulites included as lenses in mylonitic gneisses is described for the first time in a quarry located in the southern part of Campinas. Petrographic studies revealed high temperature paragenesis composed of orthopyroxene, clinopyroxene, garnet, biotite, and plagioclase. We present thermobarometric results with conditions close to the metamorphic peak, at ca. 8.7–10 kbar and 820–890 °C, which characterize these rocks as medium-pressure mafic granulites. U–]Pb zircon ages of 2134 ± 6 Ma and 2156 ± 6 Ma were obtained for the host gneisses and the mafic granulite, respectively and interpreted as the timing of their igneous crystallization. Metamorphic zircon overgrowths in the mafic granulites show a concordia age of 608 ± 3 Ma. This age is coeval with one of the several episodes of melt crystallization reported in the southern Brasilia Orogen. The Paleoproterozoic ages of ca. 2.15 Ga suggest that the protoliths of the gneisses and granulites in the Campinas region are similar to the rocks of the Pouso Alegre Complex, which represents part of the lower São Francisco plate overthrusted by the Brasilia Orogen during the Neoproterozoic orogenic collage in southeastern Brazil.
Keywords: Brasilia orogen; Geochronology; Mafic granulites; Thermobarometry